Is ChatGPT an opportunity or a threat? Preventive strategies employed by academics related to a GenAI-based LLM at a faculty of education (Journal of Applied Learning and Teaching, 2024)
Within the past decade, enormous strides have been made related to the disruptive effect of AI in education, which has grown exponentially. Recent developments in GenAI conversational models have highlighted the need to investigate this phenomenon in different contexts. This prompted me to investigate academics’ views on ChatGPT as a GenAI-based conversation tool at a faculty of education. The conversation theory is foregrounding this research. An exploratory qualitative design study foregrounded the constructivist-interpretative perspective and a sample of eight participants was purposively selected. Semi-structured interviews were generated by Microsoft Teams (transcribed), recordings were downloaded, and themes were identified as guided by the thematic analysis process. Participants echoed sentiments of the usefulness of generative AI tools in promoting or advancing teaching and learning experiences. An awareness of the ethical considerations in using generative AI tools is important before adopting chatbots. To prevent the unethical behaviour of students, it is necessary to create and adopt measures to prevent academic dishonesty. Further research is needed to build on recent gains in academic awareness of GenAI tools for teaching and learning.